Study on Disaster Mitigation in the Tambak Lorok Fisherman Village Community - Mulianingsih, Ferani; Astuti, Andarweni; Pujiati, Amin; Suprapto, Yuni (Soegijapranata Catholic University, 2025)
There are many SMEs in the area of Tambak Lorok Semarang City that produce processed seafood products. Most of them have been using simple processing and packaging methods. This study aims to analyze the use of lamicro in the community of Tambak Lorok Fisherman's Village, Semarang City.